Tarpeia the Vestal. (November 2019) - Neel, Jaclyn
Abstract: Tarpeia's role as a Vestal has become a matter of scholarly consensus in the past two decades. This article questions that consensus by suggesting that Varro and Propertius are the two major proponents of this 'Vestal version', which is not present in other major narratives such as Livy, Dionysius of Halicarnassus and Plutarch. Propertius' version in particular, which depicts Tarpeia as a Vestal in love, has been overprivileged in analyses of this myth as a dramatisation of individual identity versus loyalty to the state. Varro's account, which also includes Tarpeia's Vestal status, suggests a different interpretation: it is likely that Varro considered Tarpeia a non-Roman Vestal whose Vestal status supported the state. This version resolves certain dissonances in early Roman myth.